The influence of emotional labour strategies on customer satisfaction and word of mouth recommendations in group tours - Lee, Shin Ying; Abdul Aziz, Yuhanis; Md Sidin, Samsinar; Saleh, Rosli (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
Service employees are required to create and maintain a positive emotional disposition during a service encounter to influence the customer’s impressions and overall satisfaction. Different emotional labour strategies performed by employees will yield different effects because customers may perceive them as sincere, fake or robotic. This study aims to link the customer’s perception of the emotional labour strategies performed by service employees and the potential outcomes of these strategies on the customers. A correlation analysis is used to identify the relationship between the strategies and the customer outcome whereas a multiple regression is used to identify which of the strategies has the strongest effect on the customer outcome. Overall, the findings offer strategic marketing implications for practitioners.